Carcaça e carne de vitelos modificados da raça jersey alimentados com grão de aveia preta em substituição ao grão de milho em confinamento - Cargnelutti, Gessica Lopes (2020)
The objective was to evaluate the carcass and meat characteristics of modified Jersey calves fed with 0, 38, 73 and 100% black oat grain to replace corn grain in high grain feedlot diets. The carcasses and meat of 20 Jersey castrated calves with average initial body weight of 96.0 kg and average age of 5 months were analyzed. The experimental design used was completely randomized with four treatments (four proportions of black oats in the diet) and five replications (animals). The animals were slaughtered with similar body weight (327.5 ± 2.5 kg). The hot carcass weight and cold carcass weight did not differ (P > 0.05) between diets. The yield of hot and cold carcass was lower (P < 0.05) in diets with black oat grain compared to the diet based on corn grain. The loss of liquids during the cooling of the carcasses was greater (P < 0.05) in the oat grain diets compared to the corn-based diet. The thickness of subcutaneous fat did not differ (P > 0.05) between diets. The carcass conformation was lower (P < 0.05) for animals fed with black oat grain compared to the corn-based diet. Carcass length tended (P = 0.061) to decrease with the inclusion of black oats in the diet. The arm circumference was smaller (P < 0.05) in diets with black oats, while the others metric characteristics of the carcasses were not influenced. The carcass physical composition was not influenced (P > 0.05) by the diets. The weight (kg) of the front and special rear of the carcasses was not changed (P > 0.05) by the diets, but the weight of the ribs was lower in the diets with black oat grain compared to the corn-based diet. The substitution of corn grain for black oat grain did not change (P > 0.05) the sensory and organoleptic characteristics of the meat. The replacement of corn by black oats in high grain feedlot diets does not alter the main characteristics of economic interest of the carcasses and the meat quality of modified Jersey calves, being a technically viable feeding strategy.